Sirt1 negatively regulates FcεRI-mediated mast cell activation through AMPK- and PTP1B-dependent processes - Xian Li (Nature Portfolio, 2017)
Abstract Sirt1, a key regulator of metabolism and longevity, has recently been implicated in the regulation of allergic reactions, although the underlying mechanism remains unclear. Here we show that Sirt1 negatively regulates FcεRI-stimulated mast cell activation and anaphylaxis through two mutually regulated pathways involving AMP-activated protein kinase (AMPK) and protein tyrosine phosphatase 1B (PTP1B). Mast cell-specific knockout of Sirt1 dampened AMPK-dependent suppression of FcεRI signaling, thereby augmenting mast cell activation both in vitro and in vivo. Sirt1 inhibition of FcεRI signaling also involved an alternative component, PTP1B, which attenuated the inhibitory AMPK pathway and conversely enhanced the stimulatory Syk pathway, uncovering a novel role of this phosphatase. Moreover, a Sirt1 activator resveratrol stimulated the inhibitory AMPK axis, with reciprocal suppression of the stimulatory PTP1B/Syk axis, thus potently inhibiting anaphylaxis. Overall, our results provide a molecular explanation for the beneficial role of Sirt1 in allergy and underscore a potential application of Sirt1 activators as a new class of anti-allergic agents.